Russian-Ukraine Invasion's Effect on the Stock Market: An Event Study on Kompas 100 Index - i kadek bellyoni dwijaya; Saparman Saparman; muhammad yunus kasim (Jurnal Manajemen Bisnis Performa, 2023)
This study evaluates the reaction of the stock market to the Russian-Ukraine invasion that occurred on February 24, 2022. Using an event study approach, test the average abnormal return and the cumulative average abnormal return. The research sample uses all stocks listed on the Kompas 100 index, with a classification of 9 sectors on the Indonesia Stock Exchange (IDX). The analytical method uses a nonparametric test of difference with the Wilcoxon signed rank test. Statistical results show that there is no significant difference in the average abnormal return indexed by Kompas 100 in all study window periods, despite one of the sectors having the most significant negative impact, namely the mining sector. Cumulatively, most of the stocks show a positive trend. The performance of stocks in Indonesia is better than that of stocks in Europe, which have been significantly affected. These results provide evidence that the stock market in Indonesia is more resilient as a result of the Russia-Ukraine conflict. This research has implications for mining company investors making investment decisions in turbulent situations.Keywords: Event Studies; Market Reaction; Russian-Ukraine Invasion Penelitian ini mengevaluasi reaksi pasar saham atas invasi Rusia-Ukraina yang terjadi pada 24 februari 2022. Dengan menggunakan pendekatan studi peristiwa dengan menguji average abnormal return dan Cummulative average abnormal return. Sampel penelitian menggunakan seluruh saham yang terdaftar pada indeks Kompas 100, dengan klasifikasi 9 sektor di Bursa Efek Indonesia (BEI). Metode analisis menggunakan uji beda nonparametrik dengan uji wilcoxonesigned rank test. Hasil statistik menunjukan tidak terdapat perbedaan yang signifikan average abnormal return diindeks Kompas 100 pada semua periode jendela penelitian,salah satu sektor yang paling berdampak negatif signifikan yaitu sektor pertambangan. Secara kumulatif sebagian besar saham menunjukan trend positif. Performa saham di Indonesialebih baik dibandingkan saham di Eropa yang sangat terdampak signifikan. Hasil ini memberikan bukti bahwa pasar saham di Indonesia lebih tanguh akibat dari konflik Rusia-Ukraina. Penelitian ini memberikan implikasi bagi investorperusahaan pertambangan dalam membuat keputusan investasipada situasi yang penuh gejolak.Kata Kunci: Invasi Russia-Ukraina; Reaksi Pasar; Studi Peristiwa